EFFECTS OF DIETARY VITAMIN A AND E ON GROWTH PERFORMANCE AND ANTIOXIDANT STATUS IN BLOOD OF JUVENILE RAINBOW TROUT (ONC ORHYNCHUS MYKISS, W. 1792) E XPOSED TO FLOW RATE STRESS - G. T. Keleştemur; Y. Özdemir (Journal of Animal and Plant Sciences, 2013)
The present study investigated the effects of vitamin A and E supplementation in diets of juvenile rainbow trout subjected to two different flow rates with or without flow stress (0.9 and 2.1 l/min, respectively) on growth performance, vitamin A and E concentrations in serum, malondialdehyde (MDA) level in serum as well as plasma SOD (superoxide dismutase) activity. Fish fed with the three experimental diets (30E+A, 60E+A, –E+A ) during 12 weeks. In the unstressed groups, WG (weigth gain) of fish did not differ among the diets groups (p>0.05). Lower WG was observed in fish fed the vitamin E-free diet in stressed groups (p0.05). In the unstressed and stressed groups, serum vitamin E concentration was lowest in fish fed with A-E diets (p<0.05). In the unstressed and stressed groups, serum MDA (malondialdehyde) level was highest in fish fed the A-E diet (p<0.05). In the unstressed group, SOD activity were similarly affected by 30 and 0 mg/kg vitamin E supplemented diet groups and in both stress conditions plasma SOD (superoxide dismutase) enzyme activity increased in A+60E diet group.
Keywords: rainbow trout; stress; growth performance; antioxidan status